2023
DOI: 10.3949/ccjm.90a.22066
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive issues and multiple sclerosis: 20 questions

Abstract: Multiple sclerosis (MS) is commonly diagnosed in young adults during their reproductive years. Consequently, concerns about family planning and MS management related to pregnancy and breastfeeding are often encountered in clinical practice. Pregnancy itself is not harmful for women with MS. However, disease-modifying therapies (DMTs) have implications for reproductive planning, including stopping treatment while trying to conceive and during pregnancy, as well as managing fetal risks. People with MS and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Natalizumab should be stopped 2-3 months before conception. However, natalizumab can be continued in some circumstances (such as in patients with more active or refractory disease) until 30-34 weeks because evidence showed a higher risk of MS relapse during these special conditions and also because it does not cross the placental barrier during the first trimester of pregnancy [25][26][27]. In our study, glatiramer was the second most reported DMT, probably due to its safety in pregnancy and breastfeeding, as evaluated by regulatory agencies.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Natalizumab should be stopped 2-3 months before conception. However, natalizumab can be continued in some circumstances (such as in patients with more active or refractory disease) until 30-34 weeks because evidence showed a higher risk of MS relapse during these special conditions and also because it does not cross the placental barrier during the first trimester of pregnancy [25][26][27]. In our study, glatiramer was the second most reported DMT, probably due to its safety in pregnancy and breastfeeding, as evaluated by regulatory agencies.…”
Section: Discussionmentioning
confidence: 83%
“…In our study, most ICSRs referred to natalizumab probably because this drug was associated with a higher use during pregnancy than the other DMTs. All DMTs should have the recommended washout periods before planned conception or should be stopped when unplanned pregnancy is confirmed [25,26]. Natalizumab should be stopped 2-3 months before conception.…”
Section: Discussionmentioning
confidence: 99%
“…In select cases of women with highly active disease, a shorter interval may be considered to reduce time off therapy. These patients may discontinue contraception to attempt to become pregnant 1–3 months after rituximab or ocrelizumab, as they are eliminated by 3.5–4.5 months after dosing based on half-lives [ 75 ]. Because there is minimal placental transfer of IgG during the first trimester [ 76 ], if a woman conceives 1–3 months after the last dose of therapy, the risk of fetal exposure is low [ 77 ].…”
Section: Pregnancy and Family Planning Considerationsmentioning
confidence: 99%
“…Following recent reviews focused on female reproductive and sexual health in MS [ 20 , 24 , 31 ], we conducted a scoping review to evaluate the available literature on male reproductive and sexual health in MS. Such a comprehensive summary will facilitate current knowledge synthesis and identify existing gaps in the literature, which will guide next steps in enhancing MS clinical care and research related to male sexual and reproductive health in MS.…”
Section: Introductionmentioning
confidence: 99%